Pengaruh Lama Perendaman Biji Kedelai (Glycine max L.Merr) terhadap Karakateristik Organoletik Susu Kedelai - Mika Margareta (Balai Pelatihan Pertanian Jambi, 2021)
Soybeans (Glycine max (L) Merr.) are legumes that contain high vegetable protein, fat source, vitamins, and minerals. One of the products is soy milk. Soy milk has a strong beany flavour and a chalky mouthfeel. The flavour of soybeans in soy milk can be reduced by applying the appropriate processing techniques. One of the important steps in processing soybeans into soy milk is to soak soybeans. Studies related to soaking soybeans to soy milk are rarely found. This research was intended to find out the long-lasting influence of soybean to the organoleptic characteristics of soy milk so that the soy milk is produced by its acceptance (good acceptance). A completely randomized design was used with three treatments of soybean soaking long as follows, 6 hours, 12 hours, and 24 hours. The organoleptic data was carried out with ANOVA method at α=5% and followed by DMRT. The results showed that long soaking the soybean only affected the level of taste and overall acceptance of soy milk. In addition, the best soaking time of soybean was 12 hours because it was able to influence the taste level of flavor with the highest acceptance and the most distinct acceptance compared to other treatment with a preferred assessment score and gave the highest value of the favorite level on all parameters.